Tunable electroluminescence for pure white emission from a perovskite-based LED - Vashishtha, Parth (2022)
Halide perovskite nanocrystals are a promising candidate for lighting applications. However, the production of white light emitting diodes (LEDs) is still a major challenge due to halide ion segregation. In this work, it is demonstrated that reducing the thickness of the perovskite layer in an LED stack can modulate the recombination zone, such that a tunable emission can be obtained. This comprises of an orange electromer emission from a hole-transport layer (HTL), green electroluminescence from the perovskite active layer, and a blue monomer emission from the same HTL. Overall, a pure white emission can be achieved after successful device optimization, which is particularly challenging for LEDs in which the emission originates solely from perovskite layer. It is anticipated that this methodology could be employed on any type of green-emitting nanocrystals to fabricate white LEDs.